PEMBINAAN ROHANI KATOLIK TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS 1 MADIUN - Agustinus Supriyadi; Vinansius Fentius Lase (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Indonesian state is a state of law. Basic constitutional state is the Pancasila and the 1945 constitutional the law is one of the institutions that are needed to anticipate that the rapid developments in the human life. In combating criminal acts that appear in people's live we need a legal product that can up hold justice and can be a means of public protector. The purpose of criminal law is to prevent people committed a crime in order to create a rule of law, as the public protector (preventive purposes) and resuscitate the criminals from committing or repeating a criminal offense. In this regart, this paper was written in order to determine the extent to which the catholic spiritual guidance to inmates in prisons class 1 Madiun can develop cognitive, affective, and psychomotor and spiritual as well as the growth and development of a strong faith in Christ. Research shows that all respondents said that the spiritual guidance of the chatolic agains chatolic inmates in prisons clas 1 madiun already paying attention and very benevical to inmates. Based on research data, all or ten (10) of respondents revealed that spiritual guidance in prisons has been done. Howere, from10 (ten) of the respondent there were 8 (eight) respondents revealed already understand and follow the activities of the chatolic spiritual formation has led to repentance, maturing faith, build churches and true salvation. Therefore, the spiritual guidance of the chatolic against chatolic inmates to keep more inmates could be implemented in order to live and to discover the identity and increasingly responsible.